Integrative psychotherapy in stress management of cervical cancer patients at RSUD Dr. Moewardi Surakarta: A case study - Jhonny Prambudi Batong; Gusti Ayu Maharatih; Debree Septiawan; Teguh Prakosa (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Worldwide, cervical cancer is the second highest cause of death after breast cancer. In Indonesia, cervical cancer is ranked second among all types of cancer. Psychological distress negatively affects the mortality rate of cancer patients, and there is no stress management treatment of standard integrative psychotherapy to be carried out in the process of individual therapy in cervical cancer.Objective: To treat psychological distress in cases of cervical cancer using an integrative psychotherapy approach, create a model of factors that influence psychopathology related to psychological distress, and an integrative psychotherapy model as the basis for making modules and standard operation procedures of stress management in cervical cancer patients.Methods: This is an integrated case study with descriptive, exploratory, and exploratory qualitative approaches in two women with cervical cancer who were given integrative psychotherapy (integrative psychoeducation combined with integrative guided imagery and music), data analysis using the constant comparative method. Presentation of data using tables and graphs.Results: Two models were illustrated, a model of factors that influence psychopathology related to psychological distress and an integrative psychotherapy model in stress management of cervical cancer patients. Evaluation of decreased distress and improved related physical symptoms (pain and sleep quality).Conclusion: A model of factors that influence psychopathology related to psychological distress and an integrative psychotherapy model that can be implemented in stress management of cervical cancer patients were obtained, with sessions and types tailored to the patient’s needs.